Molecular characterization of clinical isolate of Vibrio cholera isolated from outbreaks cases in Malaysia - Patrick, Guda Benjamin; Nishibuchi, Mitsuaki; Robin, Tunung; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
A total of 32 clinical strains of Vibrio cholerae, including members of the 01 and 0139 serogroup were collected from Klang, Selangor; Penang Island; Samarahan, Sarawak and Miri, Sarawak in Malaysia. In general, all the isolates except the 0139 serotype expressed low resistance to all the antibiotics tested with their Multiple Antibiotic Resistance (MAR) indices ranged from 0.10 to 0.48. The presence of ctx gene that encoded the cholera toxin was confirmed in all these clinical isolates by polymerase chain reaction. The results from the RAPD-PCR were analyzed using the RAPDistance software (Version 1.04). From the dendrogram generated, two main groups were observed which were subdivided into two clusters each. The Selangor's isolates and the 0139 Penang's isolates formed one group whereas the Samarahan, Sarawak isolates and the Miri, Sarawak isolates made up the other group, thus delineating their different sources of origin based on their geographical location.